Effects of the exposure site on histological pulpal responses after direct capping with 2 calcium-silicate based cements in a rat model - Panruethai Trongkij; Supachai Sutimuntanakul; Puangwan Lapthanasupkul; Chitpol Chaimanakarn; Rebecca Wong; Danuchit Banomyong (Restorative Dentistry & Endodontics, 2018)
ObjectivesDirect pulp capping is a treatment for mechanically exposed pulp in which a biocompatible capping material is used to preserve pulpal vitality. Biocompatibility tests in animal studies have used a variety of experimental protocols, particularly with regard to the exposure site. In this study, pulp exposure on the occlusal and mesial surfaces of molar teeth was investigated in a rat model.Materials and MethodsA total of 58 maxillary first molars of Wistar rats were used. Forty molars were mechanically exposed and randomly assigned according to 3 factors: 1) the exposure site (occlusal or mesial), 2) the pulp-capping material (ProRoot White MTA or Bio-MA), and 3) 2 follow-up periods (1 day or 7 days) (n = 5 each). The pulp of 6 intact molars served as negative controls. The pulp of 12 molars was exposed without a capping material (n = 3 per exposure site for each period) and served as positive controls. Inflammatory cell infiltration and reparative dentin formation were histologically evaluated at 1 and 7 days using grading scores.ResultsAt 1 day, localized mild inflammation was detected in most teeth in all experimental groups. At 7 days, continuous/discontinuous calcified bridges were formed at exposure sites with no or few inflammatory cells. No significant differences in pulpal response according to the exposure site or calcium-silicate cement were observed.ConclusionsThe location of the exposure site had no effect on rat pulpal healing. However, mesial exposures could be performed easily, with more consistent results. The pulpal responses were not significantly different between the 2 capping materials.